PENDAMPINGAN TADARRUS AL-QUR'AN METODE 5T KUNCI PENINGKATAN MOTIVASI DAN INTERAKSI SANTRI TAHFIDZ LTIQ AS-SYIFA DENGAN AL-QUR'AN - Khoirul Muhtadin; Asep Warnudin (Universitas Darunnajah, Jakarta, Indonesia, 2025)
This community service activity addresses the prevalent issue in tahfidz programs in Indonesia, where memorization often overshadows understanding, implementation, and character development. The study aims to enhance motivation and deep interaction with the Al-Qur'an among 110 new tahfidz students (80 female, 30 male) at LTIQ As-Syifa, focusing on Surah Fatir verse 32. Utilizing an interactive lecture model, the